Rectal MRI Interpretation After Neoadjuvant Therapy. Issue 2 (8th September 2022) - Horvat, Natally; El Homsi, Maria; Miranda, Joao; Mazaheri, Yousef; Gollub, Marc J.; Paroder, Viktoriya
Abstract : In recent years, several key advances in the management of locally advanced rectal cancer have been made, including the implementation of total mesorectal excision as the standard surgical approach; use of neoadjuvant chemoradiotherapy in selected patients with a high risk of local recurrence, and finally, adoption of organ preservation strategies, through either local excision or nonoperative management in selected patients with clinical complete response following neoadjuvant chemoradiotherapy. This review aims to shed light on the role of rectal MRI in the assessment of treatment response after neoadjuvant therapy, which is especially important given the growing feasibility of nonoperative management. First, an overview of current neoadjuvant therapies and response assessment based on digital rectal examination, endoscopy, and MRI will be provided. Second, the use of a high‐quality restaging rectal MRI protocol will be presented. Third, a step‐by‐step approach to assessing treatment response on restaging rectal MRI following neoadjuvant treatment will be outlined, acknowledging challenges faced by radiologists during MRI interpretation. Finally, research related to response assessment will be discussed. Level of Evidence: 4 Technical Efficacy: Stage 3